BEVEL GEAR DESIGN FOR DIFFERENTIAL TRANSMISSION ON THE MIO M3 125 MOTORCYCLE - Daffa Surya Putra; Deri Teguh Santoso (Universitas Muhammadiyah Semarang, 2023)
The gears in the transmission system only get a twisting moment, there is teeth contact between the pinion and gear. Contact between rough teeth can causing non-uniform contact forces between teeth and other teeth, caused when planning is not thorough. The design of the helical gear includes calculating the dimensions, safety factor, and stresses that occur on the machine elements. This must be considered in designing helical gears so that they can be used properly. The results of the design of the helical gear pair use a 1.5mm module, a pinion head diameter of 27.2 mm while the gear is 75.4mm, the torque that occurs is 0.84 kgf, and the stress that occurs on the pinion gear is 8.33 kgf/mm2 then the gear 21,08 kgf/mm2.